Thoracic Endovascular Aortic Repair for a Ruptured Mycotic Aortic Pseudoaneurysm Secondary to Esophageal Carcinoma - Sean-Tee J. M. Lim; Stephen Murphy; Said Atyani; Michael Anthony Moloney (Case Reports in Vascular Medicine)
A 47-year-old female presented to the emergency department with new episodes of hematemesis. She had a background of unresectable T4b + N1 + M0 esophageal squamous cell carcinoma. Contrast CT thoracic aorta diagnosed a ruptured mycotic aortic pseudoaneurysm of the descending aorta, forming a life threating aorto-esophageal fistula secondary to neoplasm. Due to the high risk of fatal haemorrhage, she underwent successful emergency thoracic endovascular aortic repair (TEVAR). Mycotic aortic pseudoaneurysms are a rare and often fatal complication of esophageal carcinomas. They represent a small subsection of aorto-esophageal fistulas. Early diagnosis with cross sectional imaging and vascular control of the sentinel bleed is essential for survival. TEVAR may be used as a bridge to palliative treatment in the case of unresectable esophageal carcinoma.